Barvila za les iz tujerodnih invazivnih rastlin - Horvat, Monika (Les (Ljubljana), 2020)
The aim of the study was to produce different types of coatings based on natural dyes obtained from invasive alien plant species and residues after paper production. As a source of dye we used extracts of Rhus typhina, Japanese knotweed, Himalayan balsam and Canadian and giant goldenrod. The substrates for the application of the coating were the wood of the tree of heaven and the wood of the horse chestnut. The coatings were observed visually and the hydrophobicity of the coated surfaces was determined by the method of water droplets contact angle measurements. In addition to the transparent and brown coloured coatings, we also achieved an intense red, yellow, green, brown to violet colouring. With a combination of different components, the hydrophobic properties of the coated surfaces varied. By combining an extract of giant goldenrod flowers and 3-(triethoxysilyl)propyl isocyanate, we succeeded in producing a coating with pronounced hydrophobicity. In this research, a process for the production of coloured and transparent hydrophobic coatings was developed. Through the presence of various silane-containing molecules and the application of the coating to wooden surfaces, we changed their appearance and improved their hydrophobicity.
Keywords: Canadian goldenrod; giant goldenrod; Himalayan balsam; invasive alien plants; invazivne tujerodne rastline; Japanese knotweed; japonski dresnik; kanadska zlata rozga; naravna barvila; natural dyes; octovec; orjaška zlata rozga; staghorn sumac; žlezava nedotika